Exploring Students' Numeracy Skills in Solving Algebraic Reasoning Problems in Fifth Grade Elementary School - Anisa Agustina; Neni Mariana; Farida Istianah (Papanda Publisher, 2026)
Numeracy skills have become a central focus in contemporary mathematics education, shifting learning objectives from routine arithmetic mastery toward the ability to apply mathematical concepts in real-life contexts. In Indonesia, this shift is reinforced through the implementation of the Minimum Competency Assessment (AKM), which positions numeracy as a core student competency. This study aims to describe fifth-grade students’ numeracy skill profiles, analyze their problem-solving strategies in algebraic reasoning (AR) tasks, and identify major obstacles encountered when applying numeracy in AR contexts. A qualitative descriptive research design was employed involving 31 fifth-grade students at SDN 123 Babakan Priangan. Data were collected through a diagnostic test consisting of five contextual algebraic reasoning problems and follow-up structured interviews. The results indicate a clear polarization of students’ numeracy abilities, with 54.84% of students categorized at a poor level. Students experienced substantial difficulties in modeling proportional and inverse relationships, particularly in identifying correct scale factors and inverse operations within contextual problems. These findings suggest that targeted instructional interventions are necessary, especially to strengthen students’ abilities to translate verbal situations into algebraic models involving comparison and functional relationships. Enhancing these skills is essential to support students’ readiness for formal algebra learning in subsequent grades.